Atherosclerosis and Thrombosis: Insights from Large Animal Models. (2nd January 2011) - Vilahur, Gemma; Padro, Teresa; Badimon, Lina
Abstract : Atherosclerosis and its thrombotic complications are responsible for remarkably high numbers of deaths. The combination of in vitro, ex vivo, and in vivo experimental approaches has largely contributed to a better understanding of the mechanisms underlying the atherothrombotic process. Indeed, different animal models have been implemented in atherosclerosis and thrombosis research in order to provide new insights into the mechanisms that have already been outlined in isolated cells and protein studies. Yet, although no model completely mimics the human pathology, large animal models have demonstrated better suitability for translation to humans. Indeed, direct translation from mice to humans should be taken with caution because of the well-reported species-related differences. This paper provides an overview of the available atherothrombotic-like animal models, with a particular focus on large animal models of thrombosis and atherosclerosis, and examines their applicability for translational research purposes as well as highlights species-related differences with humans.